The Influence of Transformational Leadership Style and Teacher Performance Through Organizational Commitment As A Mediation Variable - Soelistya, Djoko; Santoso, Rahmat Agus; Wulandari, Wulandari; Selamet, Selamet (JURNAL BISNIS STRATEGI, 2024)
A good education is obtained from the quality of good teachers. And the success of education is largely determined by the performance of teachers, both teacher performance in learning planning, teacher performance in the implementation of learning, teacher performance in learning evaluation, teacher performance in the task discipline, as well as the activeness of teachers in teaching in the classroom. Research methods using data collection techniques used in this study is a questionnaire or questionnaire method. The population in the study were teachers , which amounted to 75 people. The results of this study have 7 conclusions. First, transformational leadership directly affects teacher performance. Second, Transformational Leadership directly affects organizational commitment. Third, competence directly affects organizational commitment. Fourth, competence has no direct effect on Teacher Performance. Fifth, organizational commitment has no direct effect on Teacher Performance. Sixth, Transformational Leadership directly affects the performance of teachers without going through organizational commitment as mediation. Seventh, compensation directly affects the performance of teachers through organizational commitment as mediation